HISTORY OF THE CONCEPT OF NATIONAL IDENTITY - Hamdam Umarov (Web of Journals Publishing, 2025)
This article describes the essence of the concept of national identity, the features of its formation. The relationship of national identity with the processes of spiritual development, national revival and national elevation is analyzed.
Keywords: Identity, national identity, spiritual development, national and universal values, national revival, national elevation, development strategy.